(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper provides a perspective on aspects of strategic success improvement in the corporate world with emphasis on the consumer by way of contrasting findings and provisional conclusions from research carried out in selected organisations. The effects of the study are analysed in the light of the theoretical history and the outcomes of related research. Based on these results, a series of guidelines would be given for organisations concerned with strategic success improvement geared towards the client. The paper was prepared based on analysis in international literature, interviews with managers and reviews of internal materials from selected organisations. Understanding customer behaviour is one of the foundations for creating a good business. The ever-changing environment places a toll on companies in a type of competitive consumer conduct. New goods, new values and general culture psychology need detailed analysis of market segments and customer demands.